Uzbekistānas nacionālās ekonomikas ilgtspējīga attīstība, pamatojoties uz investīciju projektiem. - Mirzoev, Sherzodjon (Latvijas Universitāte, 2018)
Izvēles tēmas aktualitāte nosaka fakts, ka laika gaitā atsevišķu reģionu un teritoriju pamatotam ilgtspējības līmenim. Tomēr lielākā daļa valstu izmanto ilgtspējīgus attīstības rādītājus, kas ļauj attīstīt ekonomiku, uzlabot sociālo un vides stāvokli. Pētījuma objekts ir Uzbekistānas Republikas tautsaimniecība, kas atrodas pārejas procesā uz tirgus ekonomiku, kur ilgtspējīgas attīstības jautājumi attīstība. Pētījuma priekšmets ir procesu un attiecību kopums, kas notiek Uzbekistānas tautsaimniecībā ilgtspējīgas attīstības sasniegšanā. Bakalaura darba mērķis ir izpētīt reformu un investīciju projektu kvalitāti Uzbekistānas tautsaimniecības kardinālas restrukturizācijas dēļ un sniegt ieteikumus, lai sasniegtu un saglabātu ilgtspējīgu attīstību ekonomiskajos, sociālajos un vides aspektos, pamatojoties uz analīzi, sniedz ieteikumus, lai paātrinātu ilgtspējīgas ekonomiskās attīstības un vides ilgtspējas sasniegšanu. Bakalaura darbs sastāv no ievada, galvenajā struktūrā bija galvenie punkti, secinājumi, ieteikumi un literatūra un izmantotie avoti.

The relevance of the topic chosen is due to the fact that to date, when all the nations of the world seek to achieve sustainable development and are at the same time guided by a variety of methods, approaches and tools on this way, there are no reasonable quantitative criteria to measure the degree of sustainability of individual regions and territories. Nevertheless, most countries use certain indicators to measure sustainable development, which allows to judge the quality of the measures and reforms for development of economy, social and environmental improvement. The object of research is the national economy of the Republic of Uzbekistan, which is in the process of transition to a market economy, where the issues of sustainable economic development are of great interest to improve the level and quality of life as the ultimate goal of development. The subject of the research is a set of processes and relationships that take place in the national economy of Uzbekistan in achieving sustainable development. The aim of the bachelor work is to study the quality of the reforms and investment projects for the cardinal restructuring of the economy of Uzbekistan and to make recommendations to achieve and maintain sustainable development in economic, social and environmental aspects and based on the analysis, to present the recommendations to accelerate the achievement of sustainable economic development and environmental sustainability. Bachelor work consists of an introduction, main body comprised main points, conclusion, recommendations and literature and sources used.
Sustainable development of national economy of uzbekistan based on investment projects
Keywords: Vadībzinātne; Sustainable development; Investment projects; Renewable energy sources; Economic, social and environmental sustainability